Meaningful managerial action planning: The financial component - J. G. Kotzé (South African Journal of Business Management, 1983)
An innovative orientation is a highly desirable characteristic of senior-middle and top management teams in business organizations. The formalized expression of such entrepreneurial flair may be developed in the form of action plans. Such plans consist of five elements, of which one, namely the financial component, is of prime importance. Three categories of action plans are distinguished and the evaluation of the anticipated financial impact of action plans within each category discussed. Finally, the integration of the anticipated financial results of action plans in the formal long- and short-term plans of an organization is described.
Keywords: 650